Coal gasification fine slag hard carbon material as well as preparation method and application thereof

By mixing the residual carbon sample in the coal gasification fine slag with inorganic oxides and performing pre-oxidation and roasting treatments, a coal gasification fine slag hard carbon material with excellent electrochemical properties is prepared, which solves the problem of existing sodium ion battery negative electrode material raw materials. The problem of instability and high cost has been achieved, and efficient and low-cost preparation of negative electrode materials for sodium-ion batteries has been achieved.

CN119361642APending Publication Date: 2025-01-24碳一(安徽)钠电材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411481811.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Among the existing sodium ion battery negative electrode materials, traditional graphite materials are not suitable. Hard carbon materials have a large layer spacing and porous structure, but the raw materials of coal-based hard carbon materials are unstable, cost high, and process complex.

Method used

By mixing residual carbon samples in coal gasification fine slag with inorganic oxides and performing pre-oxidation and roasting treatments, coal gasification fine slag hard carbon materials with excellent electrochemical properties are prepared. This method effectively improves the first Coulombic efficiency, solves the shortcoming of a large residual carbon ratio in fine residue, and avoids the problem of reduced carbon layer spacing caused by high-temperature pyrolysis.

Benefits of technology

The efficient utilization of coal-based solid waste gasification fine slag was achieved, and a low-cost, simple-process sodium-ion battery anode material was prepared, which improved the electrochemical performance and structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361642A_ABST
    Figure CN119361642A_ABST
Patent Text Reader

Abstract

The invention discloses a coal gasification fine slag hard carbon material as well as a preparation method and application thereof, and relates to the technical field of sodium ion batteries. Raw materials for preparing the coal gasification fine slag hard carbon material comprise a fine slag residual carbon sample and an inorganic oxide loaded in pores of the fine slag residual carbon sample. The preparation method comprises the following steps: dipping coal gasification fine slag in acid, filtering, washing and drying to obtain a fine slag residual carbon sample; and mixing the fine slag residual carbon sample with an inorganic oxide, pre-oxidizing and roasting to obtain the coal gasification fine slag hard carbon material. According to the method, the initial coulombic efficiency can be effectively improved through the inorganic oxide, the defect that the specific surface of residual carbon in fine residues is large can be overcome through the preparation method, and meanwhile the problem that the spacing of carbon layers in subsequent high-temperature pyrolysis is reduced is solved through introduction of the oxygen element.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a coal gasification fine slag hard carbon material and a preparation method and application thereof. Background Art

[0002] In recent years, sodium-ion batteries have become a research hotspot due to their cost advantages and abundant resource reserves, especially in the fields of energy storage, hybrid power and replacement of lead-acid batteries. As the second lightest alkali metal, sodium has similar chemical properties to lithium, but its large ionic radius makes traditional graphite negative electrode materials unsuitable for sodium ion storage. Among the common sodium-ion battery negative electrode materials, hard carbon materials have the greatest commercial potential. Their large interlayer spacing and porous structure make them considered to be ideal sodium-ion battery negative electrode materials.

[0003] The sodium storage mechanism of hard carbon includes the capacity of the slope zone caused by the ultra-large interlayer spacing and the storage of sodium by pseudo-graphitized carbon through the "interlayer embedding" mechanism. Precursors are mostly derived from biomass, coal and resins. Coal precursors are low in cost, high in carbon yield and have hard carbon properties. Research on coal-based hard carbon materials has gradually become a hot topic. Researchers mostly use coal, but coal is a composite product formed by complex geological evolution such as high temperature and high pressure. From anthracite to bituminous coal and then to lignite, its degree of metamorphism gradually decreases. Its composition structure is complex and fluctuates greatly, making it difficult to ensure a stable source of raw materials required for mass production. In addition, the high volatile matter and ash content of coal-based materials are important tests for production process technology and cost.

[0004] The production of synthetic gas by coal gasification technology is an important part of the coal chemical industry. The fine particles of coal particles in the gasifier are affected by turbulence and form fly ash with the gasification gas. After filtration, they form gasification fine slag, which is one of the coal-based solid wastes. The accumulation is large and difficult to handle. Due to the presence of considerable carbon in the future gasification, the properties are stable after high-temperature gasification. After simple purification, it has considerable development and utilization value as a sodium negative electrode carbon material.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a coal gasification fine slag hard carbon material and its preparation method and application. The doping of inorganic oxides in the coal gasification fine slag hard carbon material effectively improves the initial coulomb efficiency, solves the disadvantage of the fine slag residual carbon having a large specific surface area, and at the same time, the introduction of oxygen elements avoids the reduction of the spacing between carbon layers in the subsequent high-temperature stage, and further provides a method for preparing a negative electrode material of coal gasification fine slag, which has low cost, simple process, and is suitable for large-scale production.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a coal gasification fine slag hard carbon material, wherein the coal gasification fine slag hard carbon material comprises a fine slag carbon residue sample having inorganic oxides loaded in pores.

[0009] The single-layer distance d of the microcrystalline structure of the coal gasification fine slag hard carbon material is 002 is 0.35~0.39nm, the microcrystal stacking height Lc of the vertical layer is 2.5~3.5nm, L c / d 002 It is 7.0~9.0.

[0010] Furthermore, the coal gasification fine slag hard carbon material includes at least one of the following features (1) to (5):

[0011] (1) Specific surface area is 14 to 25 m 2 ·g -1 ;

[0012] (2) Total pore volume is 0.01 to 0.06 cm 3 ·g -1 ;

[0013] (3) Micropore volume is 0.0010~0.0030cm 3 ·g -1 ;

[0014] (4) The average pore diameter is 3 to 7 nm.

[0015] (5) The crystallite diameter La is 4.2 to 8 nm.

[0016] Furthermore, the pore characteristic parameters of the fine slag carbon residue sample include at least one of the following (1) to (4):

[0017] (1) Specific surface area is 270~450m 2 ·g -1 ;

[0018] (2) Total pore volume is 0.20 to 0.35 cm 3 ·g -1 ;

[0019] (3) Micropore volume is 0.025 to 0.065 cm 3 ·g -1 ;

[0020] (4) The average pore diameter is 3.5 to 6.0 nm.

[0021] Furthermore, the microcrystalline parameters of the fine slag carbon residue sample include at least one of the following (1) to (4):

[0022] (1) Microcrystalline structure single layer distance d 0020.340~0.370nm;

[0023] (2) The microcrystal stacking height Lc of the vertical layer is 2.00-2.55 nm;

[0024] (3)L c / d 002 5.5~7.5;

[0025] (4) The crystallite diameter La is 3.0 to 4.0 nm.

[0026] Furthermore, the fine slag carbon residue sample includes the following components in terms of mass percentage: 1-4% moisture, 0.1-20% ash, 0.5-5% volatile matter, and the remainder is fixed carbon.

[0027] Furthermore, the ash in the fine slag carbon residue sample includes the following components in terms of mass percentage: SiO2 36-55%, Al2O3 30-42%, Fe2O3 3-7%, CaO% 3-12%, MgO 0.6-1%, K2O 0.3-1%, Na2O0.4-1%, P2O5 0.2-2%, TiO2 1-4%, and SO3 1-4%.

[0028] Preferably, the loading amount of the inorganic oxide is 1 to 10 wt %.

[0029] Preferably, the inorganic oxide includes any one of aluminum oxide, iron oxide or calcium oxide, or a combination of at least two of them.

[0030] In a second aspect, the present invention provides a method for preparing the coal gasification fine slag hard carbon material as described in the first aspect, the preparation method comprising:

[0031] Take the coal gasification fine slag and acid wash it to obtain the fine slag carbon residue sample;

[0032] The fine slag carbon residue sample is mixed with an inorganic oxide, and then pre-oxidized and calcined to obtain the coal gasification fine slag hard carbon material.

[0033] Preferably, the coal gasification fine slag further includes the following pretreatment steps before pickling:

[0034] The coal gasification fine slag is dried, sieved and crushed in sequence.

[0035] Preferably, the particle size of the coal gasification fine slag obtained after screening is greater than 100 μm, preferably ≥150 μm.

[0036] Preferably, the particle size of the coal gasification fine slag obtained after the pulverization is 30 μm or less, preferably 15 to 25 μm.

[0037] Preferably, the acid includes any one of hydrochloric acid, sulfuric acid, nitric acid or hydrofluoric acid or a combination of at least two thereof, preferably a combination of hydrochloric acid and hydrofluoric acid.

[0038] Preferably, the pickling temperature is 70-90°C, and the pickling time is 6-12 hours.

[0039] Preferably, the pickling specifically comprises the following steps:

[0040] The pretreated coal gasification fine slag is firstly placed in hydrochloric acid for the first impregnation, and then placed in hydrofluoric acid for the second impregnation.

[0041] Preferably, the concentration of the hydrochloric acid is 1 to 10 mol / L, preferably 4 to 6 mol / L.

[0042] Preferably, the concentration of the hydrofluoric acid is 30-50 wt %, preferably 35-45 wt %.

[0043] Preferably, the pre-oxidation is carried out in an atmosphere of oxygen-containing gas.

[0044] Preferably, the pre-oxidation temperature is 200-300°C, and the pre-oxidation time is 3-5 hours.

[0045] Preferably, the calcination is carried out in an atmosphere of protective gas.

[0046] Preferably, the calcination temperature is 1100-1300°C, and the calcination time is 1-3 hours.

[0047] In a third aspect, the present invention provides a use of the coal gasification fine slag hard carbon material as described in the first aspect, or the coal gasification fine slag hard carbon material prepared by the preparation method as described in the second aspect in the preparation of sodium ion battery negative electrode materials or negative electrode sheets.

[0048] In a fourth aspect, the present invention provides a sodium ion battery negative electrode material, wherein the sodium ion battery negative electrode material comprises the coal gasification fine slag hard carbon material as described in the first aspect, or the coal gasification fine slag hard carbon material obtained by the preparation method as described in the second aspect.

[0049] In a fifth aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery negative electrode material as described in the fourth aspect.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] (1) The present invention effectively improves the first coulombic efficiency by loading the inorganic oxide in the pores of the fine slag carbon residue sample;

[0052] (2) The present invention solves the defect that the fine slag residual carbon ratio is large, and at the same time, the introduction of oxygen element avoids the reduction of the distance between carbon layers at the subsequent high-temperature pyrolysis temperature.

[0053] (3) The method for preparing hard carbon material from coal gasification fine slag of the present invention avoids the instability of raw materials caused by various types of coal, and has a simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0055] Figure 1 This is the SEM morphology of the fine slag carbon residue sample provided in Example 1.

[0056] Figure 2 This is the XRD diffraction fitting diagram of the fine slag carbon residue sample provided in Example 1.

[0057] Figure 3 The electrochemical performance curves of the coal gasification fine slag hard carbon materials provided in Examples 1 to 2 and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION

[0058] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0059] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0060] In a first aspect, the present invention provides a coal gasification fine slag hard carbon material, wherein the coal gasification fine slag hard carbon material comprises a fine slag carbon residue sample having inorganic oxides loaded in pores.

[0061] In the present invention, the raw materials for preparing the coal gasification fine slag hard carbon material include a fine slag carbon residue sample and an inorganic oxide loaded in the pores of the fine slag carbon residue sample; wherein the fine slag carbon residue sample is obtained by subjecting the original coal gasification fine slag to a certain deashing treatment step. The present invention utilizes the special structure of the carbon residue in the gasification fine slag to modification to prepare the coal gasification fine slag hard carbon material, but since the fine slag carbon residue sample contains a large number of pores and defects, the adsorption behavior of sodium ions in the voltage slope zone and the contact area between the material and the electrolyte will increase, thereby increasing the capacity of the slope area and reducing the first-week coulomb efficiency, which is not conducive to improving the battery energy density.

[0062] Therefore, the present invention selects to load inorganic oxides in the pores of the fine slag carbon residue sample to block the developed pores on the surface of the fine slag carbon residue, so that it forms a closed-pore structure with rich structure, and promotes the formation of unsaturated C=O groups in the material during the heat treatment process, reduces the proportion of CO groups, and promotes the transmission of sodium ions while providing abundant active sites, so that it exhibits excellent structural stability, and obtains the coal gasification fine slag hard carbon material with the following pore characteristic parameters and crystallite parameters.

[0063] As an optional embodiment of the present invention, the microcrystalline structure monolayer distance d of the coal gasification fine slag hard carbon material is 002 is 0.35~0.39nm, the microcrystal stacking height Lc of the vertical layer is 2.5~3.5nm, L c / d 002 It is 7.0~9.0.

[0064] As an optional embodiment of the present invention, the microcrystalline structure monolayer distance d of the coal gasification fine slag hard carbon material is 002 It is 0.35 to 0.39 nm, for example, it can be 0.35 nm, 0.36 nm, 0.37 nm, 0.372 nm, 0.374 nm, 0.376 nm, 0.378 nm, 0.38 nm, 0.382 nm, 0.384 nm, 0.386 nm, 0.388 nm, 0.39 nm, etc.

[0065] As an optional embodiment of the present invention, the crystallite stacking height Lc of the vertical layer of the coal gasification fine slag hard carbon material is 2.5 to 3.5 nm, for example, it can be 2.5 nm, 2.6 nm, 2.7 nm, 2.8 nm, 2.9 nm, 3.0 nm, 3.1 nm, 3.2 nm, 3.22 nm, 3.24 nm, 3.26 nm, 3.28 nm, 3.3 nm, 3.32 nm, 3.34 nm, 3.36 nm, 3.38 nm, 3.4 nm, 3.42 nm, 3.44 nm, 3.46 nm, 3.48 nm, 3.5 nm, etc.

[0066] As an optional embodiment of the present invention, the L of the coal gasification fine slag hard carbon material c / d 002 It is 7.0 to 9.0, for example, it can be 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.52, 8.54, 8.56, 8.58, 8.6, 8.62, 8.64, 8.66, 8.68, 8.7, 8.72, 8.74, 8.76, 8.78, 8.8, 8.82, 8.84, 8.86, 8.88, 8.9, 8.92, 8.94, 8.96, 8.98, 9.0, etc.

[0067] As an optional embodiment of the present invention, the coal gasification fine slag hard carbon material includes at least one of the following features (1) to (5):

[0068] (1) Specific surface area is 14 to 25 m 2 ·g -1 ;

[0069] (2) Total pore volume is 0.01 to 0.06 cm 3 ·g -1 ;

[0070] (3) Micropore volume is 0.0010~0.0030cm 3 ·g -1 ;

[0071] (4) The average pore diameter is 3 to 7 nm.

[0072] (5) The crystallite diameter La is 4.2 to 8 nm.

[0073] As an optional embodiment of the present invention, the specific surface area of ​​the coal gasification fine slag hard carbon material is 14 to 25 m 2 ·g -1 , for example, it can be 14m 2 ·g -1 、15m 2 ·g -1 、16m 2 ·g -1 、16.2m 2 ·g -1 、16.4m 2 ·g -1 、16.6m 2 ·g -1 、16.8m 2 ·g -1 、17m 2 ·g -1 、17.2m2 ·g -1 、17.4m 2 ·g -1 、17.6m 2 ·g -1 、17.8m 2 ·g -1 、18m 2 ·g -1 、18.2m 2 ·g -1 、18.4m 2 ·g -1 、18.6m 2 ·g -1 、18.8m 2 ·g -1 、19m 2 ·g -1 、19.2m 2 ·g -1 、19.4m 2 ·g -1 、19.6m 2 ·g -1 、19.8m 2 ·g -1 、20m 2 ·g -1 、21m 2 ·g -1 、22m 2 ·g -1 、23m 2 ·g -1 、24m 2 ·g -1 、25m 2 ·g -1 wait.

[0074] As an optional embodiment of the present invention, the total pore volume of the coal gasification fine slag hard carbon material is 0.01 to 0.06 cm 3 ·g -1 , for example, it can be 0.01 cm 3 ·g -1 、0.02cm 3 ·g -1 、0.03cm 3 ·g -1 、0.04cm 3 ·g -1 、0.05cm 3 ·g -1 、0.06cm 3 ·g -1 wait.

[0075] As an optional embodiment of the present invention, the micropore volume of the coal gasification fine slag hard carbon material is 0.0010 to 0.0030 cm 3 ·g -1 , for example, it can be 0.0010cm 3 ·g -1 、0.0011cm 3 ·g -1 、0.0012cm 3 ·g -1 、0.0013cm 3 ·g -1 、0.0014cm 3 ·g -1 、0.0015cm 3 ·g -1 、0.0016cm 3 ·g -1 、0.0017cm 3 ·g -1 、0.0018cm 3 ·g -1 、0.0019cm 3 ·g -1 、0.0020cm 3 ·g -1 、0.0025cm 3 ·g -1 、0.0030cm 3 ·g -1 wait.

[0076] As an optional embodiment of the present invention, the average pore size of the coal gasification fine slag hard carbon material is 3 to 7 nm, for example, it can be 3 nm, 3.5 nm, 4 nm, 4.2 nm, 4.4 nm, 4.6 nm, 4.8 nm, 5 nm, 5.2 nm, 5.4 nm, 5.6 nm, 5.8 nm, 6 nm, 6.2 nm, 6.4 nm, 6.6 nm, 6.8 nm, 7 nm, etc.

[0077] As an optional embodiment of the present invention, the crystallite diameter size La of the coal gasification fine slag hard carbon material is 4.2 to 8 nm, for example, it can be 4.2nm, 4.5nm, 5nm, 5.2nm, 5.4nm, 5.6nm, 5.8nm, 6nm, 6.2nm, 6.4nm, 6.6nm, 6.8nm, 7nm, 7.2nm, 7.4nm, 7.6nm, 7.8nm, 8nm, etc.

[0078] As an optional embodiment of the present invention, the pore characteristic parameters of the fine slag carbon residue sample include at least one of the following (1) to (4):

[0079] (1) Specific surface area is 270~450m 2 ·g -1 ;

[0080] (2) Total pore volume is 0.20 to 0.35 cm 3 ·g -1 ;

[0081] (3) Micropore volume is 0.025 to 0.065 cm 3 ·g -1 ;

[0082] (4) The average pore diameter is 3.5 to 6.0 nm.

[0083] As an optional embodiment of the present invention, the specific surface area of ​​the fine slag carbon residue sample is 270 to 450 m 2 ·g -1 , for example, it can be 270m 2 ·g -1 、280m 2 ·g -1 、300m 2 ·g -1 、320m 2 ·g -1 、340m 2 ·g -1 、350m 2 ·g -1 、360m 2 ·g -1 、370m 2 ·g -1 、380m 2 ·g -1 、385m 2 ·g -1 、386m 2 ·g -1 、387m 2 ·g -1 、388m 2 ·g -1 、389m 2 ·g -1 、390m 2 ·g -1 、391m 2 ·g -1 、392m 2 ·g -1 、393m 2 ·g -1 、394m 2 ·g -1 、395m 2 ·g -1 、400m2 ·g -1 、410m 2 ·g -1 、420m 2 ·g -1 、430m 2 ·g -1 、440m 2 ·g -1 、450m 2 ·g -1 wait.

[0084] As an optional embodiment of the present invention, the total pore volume of the fine slag carbon residue sample is 0.20 to 0.35 cm 3 ·g -1 , for example, it can be 0.20cm 3 ·g -1 、0.22cm 3 ·g -1 、0.25cm 3 ·g -1 、0.26cm 3 ·g -1 、0.27cm 3 ·g -1 、0.28cm 3 ·g -1 、0.29cm 3 ·g -1 、0.30cm 3 ·g -1 、0.31cm 3 ·g -1 、0.32cm 3 ·g -1 、0.33cm 3 ·g -1 、0.34cm 3 ·g -1 、0.35cm 3 ·g -1 wait.

[0085] As an optional embodiment of the present invention, the micropore volume of the fine slag carbon residue sample is 0.025 to 0.065 cm 3 ·g -1 , for example, it can be 0.025cm 3 ·g -1 、0.035cm 3 ·g -1 、0.045cm 3 ·g -1 、0.055cm 3 ·g -1 、0.056cm3 ·g -1 、0.058cm 3 ·g -1 、0.060cm 3 ·g -1 、0.062cm 3 ·g -1 、0.064cm 3 ·g -1 、0.065cm 3 ·g -1 wait.

[0086] As an optional embodiment of the present invention, the average pore size of the fine slag carbon residue sample is 3.5 to 6.0 nm, for example, it can be 3.5 nm, 3.6 nm, 3.7 nm, 3.8 nm, 3.9 nm, 4.0 nm, 4.02 nm, 4.05 nm, 4.08 nm, 4.1 nm, 4.12 nm, 4.15 nm, 4.18 nm, 4.2 nm, 4.5 nm, 5.0 nm, 5.5 nm, 6.0 nm, etc.

[0087] As an optional embodiment of the present invention, the microcrystalline parameters of the fine slag carbon residue sample include at least one of the following (1) to (4):

[0088] (1) Microcrystalline structure single layer distance d 002 0.340~0.370nm;

[0089] (2) The microcrystal stacking height Lc of the vertical layer is 2.00-2.55 nm;

[0090] (3)L c / d 002 5.5~7.5;

[0091] (4) The crystallite diameter La is 3.0 to 4.0 nm.

[0092] As an optional embodiment of the present invention, the microcrystalline structure single layer distance d of the fine slag carbon residue sample 002 It is 0.340 to 0.370 nm, for example, it can be 0.340 nm, 0.345 nm, 0.350 nm, 0.355 nm, 0.360 nm, 0.361 nm, 0.362 nm, 0.363 nm, 0.364 nm, 0.365 nm, 0.366 nm, 0.367 nm, 0.368 nm, 0.369 nm, 0.370 nm, etc.

[0093] As an optional embodiment of the present invention, the microcrystal stacking height Lc of the vertical layer of the fine slag carbon residue sample is 2.00-2.55nm, for example, it can be 2.00nm, 2.10nm, 2.20nm, 2.21nm, 2.22nm, 2.23nm, 2.24nm, 2.25nm, 2.26nm, 2.27nm, 2.28nm, 2.29nm, 2.30nm, 2.31nm, 2.32nm, 2.33nm, 2.34nm, 2.35nm, 2.40nm, 2.45nm, 2.50nm, 2.55nm, etc.

[0094] As an optional embodiment of the present invention, the L c / d 002 It is 5.5 to 7.5, for example, it can be 5.5, 5.6, 5.8, 6.0, 6.02, 6.04, 6.06, 6.08, 6.1, 6.12, 6.14, 6.16, 6.18, 6.2, 6.25, 6.3, 6.35, 6.4, 6.5, 6.6, 6.8, 7.0, 7.2, 7.4, 7.5, etc.

[0095] As an optional embodiment of the present invention, the crystallite diameter size La of the fine slag carbon residue sample is 3.0-4.0nm, for example, it can be 3.0nm, 3.1nm, 3.12nm, 3.14nm, 3.16nm, 3.18nm, 3.2nm, 3.22nm, 3.24nm, 3.26nm, 3.28nm, 3.3nm, 3.4nm, 3.5nm, 3.6nm, 3.7nm, 3.8nm, 3.9nm, 4.0nm, etc.

[0096] As an optional implementation mode of the present invention, the fine slag carbon residue sample comprises the following components in terms of mass percentage: 1-4% moisture, 0.1-20% ash, 0.5-5% volatile matter, and the remainder is fixed carbon.

[0097] Taking the total mass of each component in the fine slag carbon residue sample as 100%, the moisture content is 1-4%, for example, it can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, etc.

[0098] Taking the total mass of each component in the fine slag carbon residue sample as 100%, the ash content is 0.1-20%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, etc.

[0099] Taking the total mass of each component in the fine slag carbon residue sample as 100%, the content of volatile matter is 0.5-5%, for example, it can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0100] As an optional embodiment of the present invention, the ash in the fine slag carbon residue sample includes the following components in percentage by mass: SiO2 36-55%, Al2O3 30-42%, Fe2O3 3-7%, CaO% 3-12%, MgO 0.6-1%, K2O0.3-1%, Na2O 0.4-1%, P2O5 0.2-2%, TiO2 1-4%, and SO3 1-4%.

[0101] As an optional embodiment of the present invention, the loading amount of the inorganic oxide is 1 to 10 wt%, for example, it can be 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt% and the like.

[0102] As an optional embodiment of the present invention, the inorganic oxide includes any one of aluminum oxide, iron oxide or calcium oxide, or a combination of at least two of them.

[0103] In the present invention, the oxide is selected from any one of aluminum oxide, iron oxide or calcium oxide or a combination of at least two thereof, and the introduction of elements such as Fe, Al, Ca, etc. is to promote the formation of unsaturated C=O groups (stable active sites for storing Na) in the material during the controlled heat treatment process and reduce the proportion of CO groups.

[0104]

[0105] As shown in the above formula, the redox reaction can expand the interlayer spacing, which is conducive to the formation of an "adsorption-intercalation" system, as well as the combination of rapid surface reaction and intercalation reaction. While providing abundant active sites, it promotes the transmission of sodium ions and exhibits excellent structural stability.

[0106] As an optional embodiment of the present invention, the reversible specific capacity of the negative electrode material obtained by the present invention is >220mAh / g, more preferably >260mAh / g; the first cycle discharge specific capacity is >267mAh / g, more preferably >290mAh / g; the first efficiency is >85.5%, more preferably >92%.

[0107] In a second aspect, the present invention provides a method for preparing the coal gasification fine slag hard carbon material, the method for preparing the coal gasification fine slag hard carbon material comprising the following steps:

[0108] The coal gasification fine slag is placed in acid for impregnation, filtered, washed and dried to obtain a fine slag carbon residue sample;

[0109] The fine slag carbon residue sample is mixed with an inorganic oxide, and then pre-oxidized and calcined to obtain the coal gasification fine slag hard carbon material.

[0110] In the present invention, the ash in the coal gasification slag is first removed by immersing the slag in acid. The ash content can be reduced to about 0.5% after acid immersion, and a fine slag carbon residue sample with certain pore characteristic parameters and microcrystalline parameters is obtained. On this basis, the fine slag carbon residue sample is further mixed with an inorganic oxide. In this process, the inorganic oxide blocks the well-developed pores on the surface of the fine slag carbon residue sample, so that it forms a rich closed-pore structure; in addition, the introduction of elements such as Fe, Al, and Ca is to promote the generation of unsaturated C=O groups (stable active sites for storing Na) in the material during the heat treatment process, reducing the proportion of CO groups; while providing abundant active sites, it promotes the transmission of sodium ions, so that it exhibits excellent structural stability.

[0111] Therefore, the present invention avoids the problem of raw material instability caused by the complexity of coal types through the above-mentioned specific preparation method, and effectively improves the first coulomb efficiency through the oxide doping step, solves the defect of large fine slag residual carbon ratio, and at the same time, the introduction of oxygen elements in the pre-oxidation process can also avoid the problem of reduced carbon layer spacing at subsequent high-temperature pyrolysis temperature.

[0112] As an optional embodiment of the present invention, the coal gasification fine slag further includes the following pretreatment steps before impregnation:

[0113] The coal gasification fine slag is dried, sieved and crushed in sequence.

[0114] As an optional embodiment of the present invention, the particle size of the coal gasification fine slag obtained after screening is greater than 100μm, for example, it can be 101μm, 105μm, 110μm, 120μm, 130μm, 140μm, 1450μm, 150μm, 155μm, 160μm, 170μm, 180μm, 190μm, 200μm, etc., preferably ≥150μm.

[0115] As an optional embodiment of the present invention, the specific step of screening is: screening out the above-sieve particles of a specific particle size through the sieve (the above-sieve particles are coal gasification fine slag with a particle size of >100 μm, preferably ≥150 μm).

[0116] As an optional embodiment of the present invention, the particle size of the coal gasification fine slag obtained after the crushing is less than 30μm, for example, it can be 30μm, 28μm, 26μm, 25μm, 24μm, 22μm, 20μm, 19μm, 18μm, 15μm, 14μm, 12μm, 10μm, 8μm, 5μm, 1μm, etc., preferably 15-25μm.

[0117] As an optional embodiment of the present invention, the specific step of the pulverization is: the particles on the sieve obtained on the sieve are pulverized using a ball mill (to a particle size of less than 30 μm, preferably 15 to 25 μm).

[0118] As an optional embodiment of the present invention, the acid includes any one of hydrochloric acid, sulfuric acid, nitric acid or hydrofluoric acid, or a combination of at least two of them, preferably a combination of hydrochloric acid and hydrofluoric acid.

[0119] As an optional embodiment of the present invention, the immersion temperature is 70-90°C, for example, it can be 70, 72, 74, 76, 78, 80, 82, 84, 86, 88, 90°C, etc., and the immersion time is 6-12h, for example, it can be 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.

[0120] As an optional embodiment of the present invention, the impregnation specifically comprises the following steps:

[0121] The pretreated coal gasification fine slag is firstly placed in hydrochloric acid for the first impregnation, and then placed in hydrofluoric acid for the second impregnation.

[0122] As an optional embodiment of the present invention, the concentration of the hydrochloric acid is 1 to 10 mol / L, for example, it can be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, etc., preferably 4 to 6 mol / L.

[0123] As an optional embodiment of the present invention, the concentration of the hydrofluoric acid is 30-50wt%, for example, it can be 30wt%, 32wt%, 34wt%, 36wt%, 38wt%, 40wt%, 42wt%, 44wt%, 46wt%, 48wt%, 50wt%, etc., preferably 35-45wt%.

[0124] As an optional embodiment of the present invention, the pre-oxidation is carried out in an atmosphere of oxygen-containing gas.

[0125] As an optional embodiment of the present invention, the oxygen-containing gas includes air.

[0126] As an optional embodiment of the present invention, the pre-oxidation temperature is 200-300°C, for example, it can be 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, etc., and the pre-oxidation time is 3-5h, for example, it can be 3h, 3.5h, 4h, 4.5h, 5h, etc.

[0127] As an optional embodiment of the present invention, the calcination is carried out in an atmosphere of protective gas.

[0128] As an optional embodiment of the present invention, the protective gas includes any one of nitrogen, argon or helium, or a combination of at least two of them.

[0129] As an optional embodiment of the present invention, the roasting temperature is 1100-1300, for example, it can be 1100, 11200, 1150, 1180, 1200, 12200, 1250, 12800, 1300, etc., and the roasting time is 1-3h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, etc.

[0130] In a third aspect, the present invention provides a use of the coal gasification fine slag hard carbon material as described in the first aspect, or the coal gasification fine slag hard carbon material prepared by the preparation method as described in the second aspect in the preparation of a negative electrode material for a sodium ion battery.

[0131] In a fourth aspect, the present invention provides a sodium ion battery negative electrode material, wherein the sodium ion battery negative electrode material comprises the coal gasification fine slag hard carbon material as described in the first aspect, or the coal gasification fine slag hard carbon material obtained by the preparation method as described in the second aspect.

[0132] In a fifth aspect, the present invention provides a sodium ion battery, comprising the sodium ion battery negative electrode material as described in the fourth aspect.

[0133] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0134] Example 1

[0135] This embodiment provides a coal gasification fine slag hard carbon material, and the coal gasification fine slag hard carbon material is prepared by the following steps:

[0136] S1. Preprocessing:

[0137] The raw coal gasification fine slag FS was dried in a thermostatic oven at 105 to constant weight, and then the particles above 150 μm were screened out through a sieve and crushed to about 20 μm using a ball mill.

[0138] S2. Preparation of fine slag carbon residue sample:

[0139] The prepared fine slag particles were placed in a 5mol / L HCl solution (ratio 1g slag sample: 20mL acid solution), kept stirring at 80°C for 6h, filtered and washed with deionized water until neutral; then placed in a 40wt% HF solution (ratio 1g slag sample: 20mL acid solution), kept stirring at 80°C for 6h, filtered and washed with deionized water until neutral, and dried to obtain the fine slag carbon residue sample, whose SEM is as follows: Figure 1 As shown, the XRD diffraction pattern is Figure 2 shown.

[0140] S3. Preparation of coal gasification fine slag hard carbon material:

[0141] The fine slag carbon residue sample prepared by S2 is evenly mixed with Fe2O3 powder (added amount 4wt%) by ball milling; first, the temperature is raised to 260°C under N2 atmosphere, and air is switched in. The system is kept warm for pre-oxidation for 4 hours, and the air is turned off after the pre-oxidation is completed; N2 is then introduced to exhaust the gas in the system, and the temperature is raised to 1200°C for calcination and carbonization for 2 hours to obtain the coal gasification fine slag hard carbon material.

[0142] Example 2

[0143] This embodiment provides a coal gasification fine slag hard carbon material, and the coal gasification fine slag hard carbon material is prepared by the following steps:

[0144] S1. Preprocessing:

[0145] The raw coal gasification fine slag FS was dried in a thermostatic oven at 105 to constant weight, and then the particles above 150 μm were screened out through a sieve and crushed to about 20 μm using a ball mill.

[0146] S2. Preparation of fine slag carbon residue sample:

[0147] The prepared fine slag particles are placed in a 5mol / L HCl solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral; then placed in a 40wt% HF solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral, and dried to obtain the fine slag carbon residue sample.

[0148] S3. Preparation of coal gasification fine slag hard carbon material:

[0149] The fine slag carbon residue sample prepared by S2 is evenly mixed with Al2O3 powder (addition amount 4wt%) by ball milling; first, the temperature is raised to 260°C under N2 atmosphere, and air is switched in. The system is kept warm for pre-oxidation for 4 hours, and the air is turned off after the pre-oxidation is completed; N2 is then introduced to exhaust the gas in the system, and the temperature is raised to 1200°C for calcination and carbonization for 2 hours to obtain the coal gasification fine slag hard carbon material.

[0150] Example 3

[0151] This embodiment provides a coal gasification fine slag hard carbon material, which is different from the embodiment 1 only in that, in S1, the 100 μm above-sieve particles are screened out by a sieve, and the other steps are completely consistent with the embodiment 1.

[0152] Example 4

[0153] This embodiment provides a coal gasification fine slag hard carbon material, which is different from Example 1 only in that in S2, the 5 mol / L HCl solution is replaced by an equal volume of 5 mol / L H2SO4, and the 40 wt% HF solution is replaced by 40 wt% HNO3, and the other steps are exactly the same as Example 1.

[0154] Example 5

[0155] The present embodiment provides a coal gasification fine slag hard carbon material, which is different from the embodiment 1 only in that only HCl solution is used for ash removal in S2, specifically: the prepared fine slag particles are placed in a 5 mol / L HCl solution (ratio 1 g slag sample: 20 mL acid solution), kept stirring at 80°C for 12 h, filtered, washed with deionized water until neutral, and dried to obtain the fine slag residual carbon sample; the other steps are exactly the same as those in the embodiment 1.

[0156] Example 6

[0157] The present embodiment provides a coal gasification fine slag hard carbon material, which differs from the embodiment 1 only in that only HF solution is used for ash removal in S2, specifically: the prepared fine slag particles are placed in a 40wt% HF solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 12h, filtered, washed with deionized water until neutral, and dried to obtain the fine slag residual carbon sample; the other steps are exactly the same as those in the embodiment 1.

[0158] Example 7

[0159] This embodiment provides a coal gasification fine slag hard carbon material, which is different from Embodiment 1 only in that, in S3, Fe2O3 powder is replaced by CaO of equal mass; the other steps are exactly the same as Embodiment 1.

[0160] Example 8

[0161] This embodiment provides a coal gasification fine slag hard carbon material, which is different from Embodiment 1 only in that in S3, Fe2O3 powder is replaced by MgO of equal mass; other steps are exactly the same as Embodiment 1.

[0162] Comparative Example 1

[0163] This comparative example provides a coal gasification fine slag hard carbon material, and the coal gasification fine slag hard carbon material is prepared by the following steps:

[0164] S1. Preprocessing:

[0165] The raw coal gasification fine slag FS was dried in the sun and then crushed to about 20 μm using a ball mill.

[0166] S2. Preparation of fine slag carbon residue sample:

[0167] The prepared fine slag particles are placed in a 5mol / L HCl solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral; then placed in a 40wt% HF solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral, and dried to obtain the fine slag carbon residue sample.

[0168] S3. Preparation of coal gasification fine slag hard carbon material:

[0169] The fine slag carbon residue sample prepared by S2 was first heated to 260°C under N2 atmosphere, and then switched to air. The mixture was kept warm for pre-oxidation for 4 hours, and the air was turned off after the pre-oxidation. N2 was then introduced to exhaust the gas in the system, and then the temperature was raised to 1200°C for calcination and carbonization for 2 hours to obtain the coal gasification fine slag hard carbon material.

[0170] Comparative Example 2

[0171] This comparative example provides a coal gasification fine slag hard carbon material, and the coal gasification fine slag hard carbon material is prepared by the following steps:

[0172] S1. Preprocessing:

[0173] The raw coal gasification fine slag FS was dried in the sun, and then the particles under 44 μm were screened out through a sieve, and then the particles were crushed to about 20 μm using a ball mill.

[0174] S2. Preparation of fine slag carbon residue sample:

[0175] The prepared fine slag particles are placed in a 5mol / L HCl solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral; then placed in a 40wt% HF solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral, and dried to obtain the fine slag carbon residue sample.

[0176] S3. Preparation of coal gasification fine slag hard carbon material:

[0177] The fine slag carbon residue sample prepared by S2 is evenly mixed with Fe2O3 powder (added amount 4wt%) by ball milling; first, the temperature is raised to 260°C under N2 atmosphere, and air is switched in. The system is kept warm for pre-oxidation for 4 hours, and the air is turned off after the pre-oxidation is completed; N2 is then introduced to exhaust the gas in the system, and the temperature is raised to 1200°C for calcination and carbonization for 2 hours to obtain the coal gasification fine slag hard carbon material.

[0178] Comparative Example 3

[0179] This comparative example provides a coal gasification fine slag hard carbon material, and the coal gasification fine slag hard carbon material is prepared by the following steps:

[0180] S1. Preprocessing:

[0181] The raw coal gasification fine slag FS was dried in a thermostatic oven at 105 to constant weight, and then the particles above 150 μm were screened out through a sieve and crushed to about 20 μm using a ball mill.

[0182] S2. Preparation of fine slag carbon residue sample:

[0183] The prepared fine slag particles are placed in a 5mol / L HCl solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral; then placed in a 40wt% HF solution (ratio 1g slag sample: 20mL acid solution), kept stirring at a constant temperature of 80 for 6 hours, filtered, and washed with deionized water until neutral, and dried to obtain the fine slag carbon residue sample.

[0184] S3. Preparation of coal gasification fine slag hard carbon material:

[0185] The fine slag carbon residue sample prepared by S2 is evenly mixed with Fe2O3 powder (addition amount 4wt%) by ball milling; after N2 is introduced to exhaust the gas in the system, the temperature is raised to 1200°C and calcined and carbonized for 2h to obtain the coal gasification fine slag hard carbon material.

[0186] Comparative Example 4

[0187] The present embodiment provides a coal gasification fine slag hard carbon material, which differs from the embodiment 1 only in that, in S3, the pre-oxidation parameter conditions are different from those in the embodiment 1, specifically: firstly, the temperature is raised to 180°C under a N2 atmosphere, and then the air is switched in, and the pre-oxidation is carried out for 6 hours at a heat preservation temperature, and then the air is turned off after the pre-oxidation is completed; the other steps are exactly the same as those in the embodiment 1.

[0188] Comparative Example 5

[0189] The present embodiment provides a coal gasification fine slag hard carbon material, which differs from the embodiment 1 only in that, in S3, the pre-oxidation parameter conditions are different from those in the embodiment 1, specifically: firstly, the temperature is raised to 260°C under a N2 atmosphere, and then the air is switched in, and the pre-oxidation is carried out for 2 hours at a heat preservation temperature, and then the air is turned off after the pre-oxidation is completed; the other steps are exactly the same as those in the embodiment 1.

[0190] Test Example 1

[0191] Test samples: original coal gasification fine slag FS, fine slag carbon residue samples provided in Example 1 and S2 in Examples 3 to 6, and fine slag carbon residue samples provided in Comparative Examples 1 to 2; coal gasification fine slag hard carbon materials provided in Examples 1 to 10, and coal gasification fine slag hard carbon materials provided in Comparative Examples 1 to 3.

[0192] Test method:

[0193] (1) Hole characteristic parameters:

[0194] The low-temperature nitrogen adsorption method was used in the United States MICROMERITICS ASAP2020 fully automatic physical adsorption instrument to determine the specific surface area and pore volume of the material; the test conditions were: adsorption temperature was -195.8℃ (77.35K), degassing temperature was 150, degassing time was 6h, specific surface area analysis method was BET method, and pore size analysis model was BJH model.

[0195] (2) XRD test:

[0196] The XRD instrument used in the microstructure analysis experiment of residual carbon in gasification fine slag is Beijing Puxi General MSALXD-3 X-ray powder diffractometer. The experimental scanning range is: 12~65°; scanning speed is: 2° / min; step length: 0.02°; incident wavelength λ=1.5406; the fine slag material is screened to obtain samples, which are ground and sieved below 100 mesh, and immediately sent to the laboratory, placed on a glass slide on a sample rack, and sent to the X-ray diffractometer for XRD experiment.

[0197] (3) Microcrystal parameters:

[0198] There are two large "steamed bun-shaped" unit cell diffraction peaks in the range of 15-55°, corresponding to the 002 peak and the 100 peak. (The 002 peak of natural graphite is located at 26.6°). In order to compare the microcrystalline structure of the residual carbon material, the 002 peak and the 100 peak in the diffraction angle band of 12-35° and 35-50° were fitted by Origin.

[0199] In order to make a more accurate comparison and reduce errors, the 12-65° data is first baseline-subtracted, and then the 002 peak and 100 peak are fitted by peak fitting. The sample microcrystalline structure information is specifically calculated according to Bragg's law and Scherrer's law:

[0200] The calculation formula is as follows:

[0201] La=k1λ / (β 100 cosθ 100 )

[0202] Lc=k2λ / (β 002 cosθ 002 )

[0203] d 002 =λ2sinθ 002

[0204] Where: d 002 is the distance between single layers of microcrystalline structure; Lc is the microcrystalline stacking height of the vertical layer; La is the diameter of the microcrystalline; θ 002 ,θ 100 is the Bragg diffraction angle; β 002 , β 100 is the half-peak width; λ is the X-ray wavelength, nm; k is the shape factor, k1=1.84, k2=0.94.

[0205] (4) Material electrochemical performance test:

[0206] Active material: SP: CMC: SBR = 94: 2: 1.5: 2.5, weigh the negative electrode material, SP, CMC, SBR respectively, mix them evenly in deionized water to make slurry; apply the mixed slurry on the aluminum foil current collector, bake it in an oven at 80 for 1 hour, take it out and cool it to room temperature. Adjust the rolling gap to roll the pole piece.

[0207] The rolled pole piece was cut into small discs with a diameter of 14 mm and weighed as m1. Similarly, the aluminum foil current collector was cut into aluminum foil discs with a diameter of 14 mm and weighed as m2. Among them, (m1-m2)×0.94 is the mass of the active material, recorded as m3. The weighed small discs were then placed in an 80 degree oven and vacuum-dried for 12 hours and then transferred to a glove box. Sodium sheets were used as counter electrodes and auxiliary electrodes (electrolyte 1M NaPF6 / EC:DMC:DEC=3:2:2) and fiber diaphragms were used as diaphragms. Sodium ion button batteries were assembled in a glove box with oxygen and water content less than 0.01 ppm. After standing for 12 hours, the electrochemical performance was tested at a constant current on the Wuhan Blue Electric Battery Test System.

[0208] The test method adopts the first-effect test system: stand for 2 hours, discharge to 0.000v at 0.1C, discharge to 0.000v at 0.08C, discharge to 0.000v at 0.05C, discharge to 0.000v at 0.02C, stand for 5 minutes, charge to 2.0V at 0.1C, and stand for 5 minutes.

[0209] The specific test results are shown in Tables 1 to 5 below:

[0210] Table 1

[0211]

[0212] Table 2

[0213]

[0214] Table 3

[0215]

[0216]

[0217]

[0218] Table 4

[0219]

[0220]

[0221]

[0222] Table 5

[0223]

[0224]

[0225] As shown in the table above and Figure 3 -As shown in the electrochemical performance curve, the present invention effectively improves the initial coulomb efficiency and the electrochemical performance of the negative electrode material by loading the inorganic oxide in the pores of the fine slag residual carbon sample; the present invention solves the defect of the fine slag residual carbon having a large specific surface area, and at the same time, the introduction of oxygen element avoids the reduction of the carbon layer spacing at the subsequent high-temperature pyrolysis temperature. In the preparation process of the hard carbon negative electrode material provided by the present invention, the coal-based solid waste gasification fine slag with a specific particle size range is selected as the raw material, and after acid leaching, a more developed pore structure is presented, and the electrochemical performance of the obtained negative electrode material is further improved.

[0226] The present invention also requires pre-oxidation before carbonization of coal-based hard carbon. By regulating the pre-oxidation parameters including pre-oxidation temperature, time, concentration, etc., the directional growth of graphite domains can be suppressed during the carbonization process, thereby constructing more turbostratic graphite microstructures and further forming abundant pores to accommodate more sodium ions, and the obtained negative electrode material exhibits more excellent electrochemical performance.

[0227] The method for preparing the coal gasification fine slag hard carbon material of the present invention avoids the problem of raw material instability caused by the variety of coal types, has a simple process and low cost. At the same time, the present invention develops a new way to apply coal-based solid waste gasification fine slag to the high value-added field of negative electrode materials, and reasonably and effectively improves the carbon utilization rate of gasification fine slag.

[0228] The present invention utilizes the special structure of residual carbon in gasified fine slag for the first time, and prepares hard carbon negative electrode material through simple modification. The material exhibits excellent electrochemical properties, and its specific capacity and first efficiency are significantly improved.

[0229] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A coal gasification fine slag hard carbon material, characterized in that: The coal gasification fine slag hard carbon material includes a fine slag carbon residue sample with inorganic oxides loaded in the pores; The single-layer distance d of the microcrystalline structure of the coal gasification fine slag hard carbon material is 002 is 0.35~0.39nm, the microcrystal stacking height Lc of the vertical layer is 2.5~3.5nm, L c / d 002 It is 7.0~9.

0.

2. The coal gasification fine slag hard carbon material according to claim 1, characterized in that: The coal gasification fine slag hard carbon material comprises at least one of the following features (1) to (5): (1) Specific surface area is 14 to 25 m 2 ·g -1 ; (2) Total pore volume is 0.01 to 0.06 cm 3 ·g -1 ; (3) Micropore volume is 0.0010~0.0030cm 3 ·g -1 ; (4) The average pore diameter is 3 to 7 nm; (5) The crystallite diameter La is 4.2 to 8 nm.

3. The coal gasification fine slag hard carbon material according to claim 1, characterized in that: The pore characteristic parameters of the fine slag carbon residue sample include at least one of the following (1) to (4): (1) Specific surface area is 270~450m 2 ·g -1 ; (2) Total pore volume is 0.20 to 0.35 cm 3 ·g -1 ; (3) Micropore volume is 0.025 to 0.065 cm 3 ·g -1 ; (4) The average pore diameter is 3.5 to 6.0 nm; And / or, the microcrystalline parameters of the fine slag carbon residue sample include at least one of the following (1) to (4): (1) Microcrystalline structure single layer distance d 002 0.340~0.370nm; (2) The microcrystal stacking height Lc of the vertical layer is 2.00-2.55 nm; (3)L c / d 002 5.5~7.5; (4) The crystallite diameter La is 3.0-4.0 nm; And / or, the fine slag carbon residue sample comprises the following components by mass percentage: 1-4% moisture, 0.1-20% ash, 0.5-5% volatile matter, and the remainder is fixed carbon; And / or, the ash in the fine slag carbon residue sample includes the following components in terms of mass percentage: SiO2 36-55%, Al2O3 30-42%, Fe2O3 3-7%, CaO% 3-12%, MgO 0.6-1%, K2O 0.3-1%, Na2O0.4-1%, P2O5 0.2-2%, TiO2 1-4%, SO3 1-4%.

4. The coal gasification fine slag hard carbon material according to claim 1, characterized in that: The loading amount of the inorganic oxide is 1 to 10 wt %; Preferably, the inorganic oxide includes any one of aluminum oxide, iron oxide or calcium oxide, or a combination of at least two of them.

5. A method for preparing a hard carbon material from coal gasification fine slag according to any one of claims 1 to 4, characterized in that: include: Take the coal gasification fine slag and acid wash it to obtain the fine slag carbon residue sample; The fine slag carbon residue sample is mixed with an inorganic oxide, and then pre-oxidized and calcined to obtain the coal gasification fine slag hard carbon material.

6. The method for preparing coal gasification fine slag hard carbon material according to claim 5, characterized in that: The coal gasification fine slag further includes the following pretreatment steps before pickling: The coal gasification fine slag is dried, sieved and crushed in sequence; Preferably, the particle size of the coal gasification fine slag obtained after screening is >100 μm, preferably ≥150 μm; Preferably, the particle size of the coal gasification fine slag obtained after the pulverization is less than 30 μm, preferably 15 to 25 μm; Preferably, the acid includes any one of hydrochloric acid, sulfuric acid, nitric acid or hydrofluoric acid or a combination of at least two thereof, preferably a combination of hydrochloric acid and hydrofluoric acid; Preferably, the pickling temperature is 70-90°C, and the pickling time is 6-12 hours; Preferably, the pickling specifically comprises the following steps: The pretreated coal gasification fine slag is firstly placed in hydrochloric acid for a first immersion, and then placed in hydrofluoric acid for a second immersion; Preferably, the concentration of the hydrochloric acid is 1 to 10 mol / L, preferably 4 to 6 mol / L; Preferably, the concentration of the hydrofluoric acid is 30-50 wt %, preferably 35-45 wt %.

7. The method for preparing coal gasification fine slag hard carbon material according to claim 5, characterized in that: The pre-oxidation is carried out in an atmosphere of oxygen-containing gas; Preferably, the pre-oxidation temperature is 200-300°C, and the pre-oxidation time is 3-5 hours; Preferably, the calcination is carried out in an atmosphere of protective gas; Preferably, the calcination temperature is 1100-1300°C, and the calcination time is 1-3 hours.

8. Use of the coal gasification fine slag hard carbon material according to any one of claims 1 to 4, or the coal gasification fine slag hard carbon material prepared according to the preparation method according to any one of claims 5 to 7 in preparing a negative electrode material or a negative electrode sheet for a sodium ion battery.

9. A negative electrode material for a sodium ion battery, characterized in that: The sodium ion battery negative electrode material comprises the coal gasification fine slag hard carbon material according to any one of claims 1 to 4, or the coal gasification fine slag hard carbon material prepared according to the preparation method according to any one of claims 5 to 7.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the sodium ion battery negative electrode material as claimed in claim 9.